Utilizing Basic Digital Photography Techniques on the Farm - Ricky Telg; Carly Barnes; Adrienne Boyette (EDIS)
This 3-page fact sheet focuses on plant and livestock photography and caption writing and outlines tips for taking digital photographs on the farm using a basic digital or cell phone camera. Written by Ricky Telg, Carly Barnes, and Adrienne Boyette, and published by the UF Department of Agricultural Education and Communication, August 2011.